Apple is my sign - Riskind, Mary. (Boston : Houghton Mifflin, 1981)
A 10-year-old boy returns to his parents' apple farm for the holidays after his first term at a school for the deaf in Philadelphia.
Keywords: Deaf people -- Juvenile fiction; People with disabilities -- Juvenile fiction